A double-dysprosocenium single-molecule magnet bound together with neutral ligands. Issue 42 (22nd April 2020) - Evans, Peter; Reta, Daniel; Goodwin, Conrad A. P.; Ortu, Fabrizio; Chilton, Nicholas F.; Mills, David P.
Abstract : Double dysprosocenium: we report a dinuclear complex containing two dysprosocenium cations, unusually held together by electrostatic interactions with neutral molecules. Abstract : A dinuclear dysprosocenium dication has been synthesised that is bound together by weak interactions between Dy(Cp*)2 + fragments and neutral NEt3 AlMe3 molecules. The axiality of the Dy 3+ crystal fields are perturbed by these equatorial interactions but a relatively large effective barrier to magnetisation reversal of 860(60) cm −1 and magnetic hysteresis up to 12 K are observed.